2019
DOI: 10.15171/jrip.2019.38
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) and IL-17 levels are associated with disease activity in systemic lupus erythematosus patients with and without nephritis

Abstract: Introduction: Lupus nephritis (LN) is one of the most severe signs of systemic lupus erythematosus (SLE) and rapid diagnosis of kidney damage remains an important concern for LN. Objectives: The aim of this study was to investigate the association of the serum levels of tumor necrosis factor-like weak inducer of apoptosis (TWEAK) and interleukin 17 (IL-17) with SLE severity, renal involvement, and other clinical manifestations in lupus patients. Patients and Methods: In order to determine a better biomarker fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Tumor necrosis factor (TNF)-alpha, interferon-gamma, and members of the interleukin family are among the major inflammatory cytokines investigated in this context [7][8][9][10]. Proinflammatory cytokine soluble TNF-like weak inducer of apoptosis (TWEAK), which belongs to the TNF superfamily, is associated with many different inflammatory disorders [11][12][13][14][15]. TWEAK (30 kD, 249 aa), which is synthesized as a membranebound protein in the endoplasmic reticulum, is processed Objectives: Behçet's disease (BD) is a chronic multisystemic inflammatory disorder and is associated with many inflammatory processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor necrosis factor (TNF)-alpha, interferon-gamma, and members of the interleukin family are among the major inflammatory cytokines investigated in this context [7][8][9][10]. Proinflammatory cytokine soluble TNF-like weak inducer of apoptosis (TWEAK), which belongs to the TNF superfamily, is associated with many different inflammatory disorders [11][12][13][14][15]. TWEAK (30 kD, 249 aa), which is synthesized as a membranebound protein in the endoplasmic reticulum, is processed Objectives: Behçet's disease (BD) is a chronic multisystemic inflammatory disorder and is associated with many inflammatory processes.…”
mentioning
confidence: 99%
“…When TWEAK binding to Fn14 induces a proinflammatory response by activating the nuclear factor kappa B (NF-B) signal transduction system [20,21]. Circulating sTWEAK concentrations have been determined for approximately the past 15 years, and it has been suggested that sTWEAK concentrations can be used as a novel biomarker in a wide variety of diseases [13][14][15][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%